FROM NATURAL LANGUAGE PROCESSING TO SENTIMENT ANALYSIS - Campos, Edson; de Lima Piteli Picchi, Mirela de Lima Piteli (Revista Interface Tecnológica, 2023)
This article explained fundamental concepts of Natural Language Processing and its various tools that have been improved over the years and are present every day in people's routines. A  literature review and analysis was carried out on Natural Language Processing, Machine Learning and Computational Linguistics, showing how from textual analysis one can arrive at complex machine learning algorithms, aiming at conceptualizing and narrowing down to the point of exemplify the concept and application of Sentiment Analysis in an application. The evolution of natural language processing makes the evolution of machine learning tools necessary, as they are essential parts within a chain of events that has been improving with impressive speed. From the concept to the final result, it is possible to verify how comprehensive and full of ramifications this theme is and, through an objective analysis, verify that the path to the future passes through machine learning and machine understanding of human language.
Keywords: Natural Language Processing; Machine Learning; Sentiment Analysis